Serum 25-hydroxyvitamin D concentrations and their impact on all-cause mortality in Parkinson’s disease: insights from National Health and Nutrition Examination Survey 1999–2020 data - Yong, Yufei; Dong, Hui; Zhou, Zhen; Zhu, Yan; Gu, Meiling; Li, Wenxiao (Frontiers in Nutrition, 2024)
Background and Purpose: This study explores the relationship between serum 25-hydroxyvitamin D (25(OH)D) levels and mortality among Parkinson’s Disease (PD) patients, providing evidence for the potential benefits of vitamin D (VD) supplementation. Methods: PD patients were collected from the NHANES database from 1999 to 2020. These patients were categorized based on their serum 25(OH)D levels: deficiency, insufficiency, and sufficiency. We compared demographic information and analyzed mortality data from the National Death Index. A restricted cubic spline model assessed the nonlinear association between 25(OH)D levels and mortality, complemented by multivariable Cox regression analysis. Consistency of results was checked through subgroup analysis. Results: The study included 364 PD patients: 87 (23.9%) with VD deficiency, 121 (33.2%) with insufficiency, and 156 (42.9%) with sufficiency. Demographically, 46.4% were male, and 56% were over 65 years. The deficiency group predominantly consisted of Mexican Americans (53.1%), had lower income levels, a higher unmarried rate, and increased liver disease incidence. The analysis showed a U-shaped curve between 25(OH)D levels and mortality risk, with the lowest risk at 78.68 nmol/L (p-non-linear = 0.007, p-overall = 0.008). Kaplan-Meier analysis found the highest survival rates in patients with 25(OH)D levels between 75-100 nmol/L (p = 0.039). Compared to this group, patients with levels below 50 nmol/L had a 3.52-fold increased mortality risk (95%CI = 1.58-7.86, p = 0.002), and those above 100 nmol/L had a 2.92-fold increase (95%CI = 1.06-8.05, p = 0.038). Age-specific subgroup analysis (p = 0.009) revealed that both very low (<50 nmol/L) and high (>100 nmol/L) levels increased mortality risk in patients under 65, while levels below 75 nmol/L raised mortality risk in older patients. Conclusion: Serum 25(OH)D levels are nonlinearly linked to mortality in PD patients, with optimal survival rates occurring at 75-100 nmol/L. Deviations from this range increase the risk of death.